Eugenics and Medical Specialties: The 1930s - Mota, André (Circumscribere International Journal for the History of Science, 2009)
The aim of this study (article) is to revise the preponderant view that the Medelian (or negative) eugenics had been marginalized among the Brazilian scholars, therefore the environmental eugenics becoming the only one accepted, practiced and wide spread. type of eugenics. This reading comes from the fact that issues concerning eugenics were approached in the medical and health institutions, in the 1930s in São Paulo, as scientific technology incorporated by the diverse medical specializations that were trying to get institutionalized. The eugenic arguments of the latter were supported by the thesis of the hereditary degeneration that defended the restrictions through pre-nuptial examinations, sterilization and even suppression of individuals. This debate reached into practice and teaching of nursing, far longer than the 1930s. Concerning the nursing field, we believe that the current historiography should be deeply analyzed, not just with regard to the documentation of such a decade which had presented an apocryphal discourse on eugenics, but also on the development of such field allowing a broader debate on the current practice of eugenics